Tectonic geomorphological evidence of late Quaternary segmented activity along the northern margin fault of Lajishan - ZHANG Lijun; YUAN Daoyang; LI Hongqiang; SU Qi; SU Ruihuan; CHEN Yanwen; WEN Yameng (Dizhi lixue xuebao)
Objective  The Lajishan–Jishishan orogenic belt represents a significant arc-shaped tectonic zone formed by northeastward compressional expansion along the northeastern margin of the Tibetan Plateau, jointly controlled by two compressional thrust fault zones: the North Lajishan Fault and the South Lajishan fault. Since the Late Cenozoic, intense tectonic activities in the Lajishan area have created a prominent basin–range coupled geomorphological pattern, making it an ideal region for investigating the geomorphic evolution and the tectonic dynamics through structural geomorphological approaches.   Methods  Based on a 30-m-resolution digital elevation model (DEM), this study employs the ArcGIS and MatLab platforms with plugin tools and open-source code packages to extract channel steepness indices (Ksn) from 105 medium- and small-sized rivers on the hanging wall of the North Lajishan Fault (including the East Jishishan Fault), along with hypsometric integrals (HI) from 54 watersheds along the fault zone.   Results  The Ksn distribution reveals an overall west-to-east increasing trend in uplift rates along the North Lajishan fault, with a notable low-value anomaly in its central segment. Statistical analysis of Ksn demonstrates clear segmentation characteristics, indicating that the eastern section of northern Lajishan and the Jishishan section exhibit the highest uplift rate and strongest tectonic activity. HI spatial distribution patterns along the North Lajishan fault show multiple high-value zones within piedmont basins. Integrated with geological surveys and petroleum exploration profiles, these findings suggest that during the Late Quaternary, the North Lajishan fault has not only remained active but also propagated northeastward into the Xining–Minhe and Linxia basins, exhibiting thrust fault–fold deformation features.   Conclusion  (1) The tectonic geomorphological evolution of the North Lajishan Fault (including the eastern margin of Jishishan) is obviously different, and it tends to gradually become younger from west to east. The geomorphological evolution of the northern margin of Lajishan has discrete differences, which can be attributed to three sections: a western, a middle, and an eastern section, which includes the northern margin of Jishishan. Among them, the tectonic activity of the latter section is the latest and most intense, consistent with the long-term tectonic evolution. This confirms the rationality of the geomorphological parameter extraction results and is also a geomorphological response to the differential tectonic activity in this area. (2) The tectonic activity characteristics of the northern margin of Lajishan (including the eastern margin of Jishishan) adhere to the geomorphological evolution law and also have segmental differences. It is believed that the North Lajishan Fault (including the East Jishishan Fault) has strong tectonic activity from west to east. Specifically, the uplift rate of the western section of the northern margin of Lajishan is stable. The tectonic activity may be superimposed on the strike-slip component of the Riyueshan Fault in addition to the regional extrusion uplift, which was active in the Late Pleistocene and dominated by left-handed strike-slip and thrust. The middle section of the northern margin of Lajishan (NE-trending bulge section) has the lowest tectonic uplift rate, and the fault in this section is dominated by extrusion thrust with a late Pleistocene activity; it is little affected by the Riyueshan fault. The eastern section of the northern margin of the Lajishan-Jishishan section (the fault arc protrudes to the south-east turning section) has strong tectonic activity with Holocene fault activity; its nature is mainly thrust with dextral components. Significance In addition to its late Quaternary activity, the North Lajishan Fault (including the East Jishishan Fault) tends to expand and develop into the piedmont basin. Combined with the comprehensive interpretation of field geological surveys and oil exploration sections, it is believed that the fault extends to the interior of the Xining–Minhe Basin to form a reverse fault–fold belt. Its latest tectonic activity may have triggered more than 10 moderate–strong earthquakes. Attention should be paid to this tectonic activity and the related seismicity in those basin.